Halimaw a campaign for comic spin-off from a popular teleserye series to create audience investment towards the story instead of its characters - Daquigan, Majaraya Ysa F.
The Philippines is no stranger in the romance genre, with the awit and corrido derived from medieval Spanish literature, romance is a genre known to many Filipinos. A popular genre at its own right throughout history, the romance genre and its narrative have transcended beyond its fantastical and escapistnature of storytelling from its transformation from the Spanish "Comedia" towards a contemporary storytelling such as. The romance genre infuses itself on commentaries of social issues prevalent in society, transforming the romance genre as a way for understanding the complicated complexities of history or life. Going beyond literature, the romance genre is now prominent in movies, television, comics and other mediums. This research aims on understanding the romance genre and its narrative through its structure; story and themes present and then associate these understanding in a Philippine context through television medium of teleseryes. The research also aims to provide insights if the repetition of conventions in storytelling through narrative and characters, the teleseryes affect the audience's perception towards their own life. This will also see if the audience in question use the information they gain from watching teleseryes affect the way how they use and tackle issue in real life. Through analysis of current popular teleseryes in the Philippines, there are indeed similarities in narrative structure, themes and characterization and are consistent depending n the television network they air. With the analysis of the narrative, this is then analysed along with the interviews network they air. With the analysis of the narrative, this is then analysed along with the interviews of the house helper demographic in seeing if the romance genre int he television medium affected their perception. Through analysis, there are effects towards the audience internally, by being relatable and similar of their real life situations. With some aspiring to be their favorite characters in specifics parts of their personality or as a whole. Whether this is through the plot, the characters, or even both, they use the information they obtain from the teleseryes' bigger than life romance narrative as a preparation in possibility of a similar situation in the teleserye is encountered in their own life. This then gives rise to the conclusion of the romance narrative in teleseryes as not only just an enjoyable pastime for many Filipino viewers, but also helps them understand in ways how they can deal similar situations in society in real life. This thesis aims to create more investment towards the shows they watch using the comic book medium instead of a televised medium. the comic book medium is a popular medium in the Philippines and is really available in digital or printed format. This'll help in creating a more in-depth and further understanding towards the world behind the teleseryes they watch, at the same time help develop reading comprehension and vocabulary skills. Further look into the research shows the investment towards the actors or the character's they play as the main reasoning why they watch teleseryes. The comic book is aimed at remedying the focused investment of the audience towards the actors or the characters they portray towards an equal focus of both character and story, creating an appreciation towards Filipino made narratives and the potential for expanding for a wider audience.